Pengaruh Kualitas Pelayanan, Kualitas Produk, Dan Bauran Promosi Terhadap Keputusan Pembelian Konsumen Di Waroeng OM Kota Malang - Agus Mubarok; Agus Widarko; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of service quality, product quality and promotion mix on purchasing decisions for Waroeng Om products, Malang City. The location of this research was carried out on the community and students in Malang City who became consumers of Waroeng Om Malang City. This research is a quantitative research. This research uses a case study method where data is obtained by distributing questionnaires to the public and students in Malang City who were selected by purposive sampling. Determination of the number of samples using the Maholtra formula and the results obtained were 85 respondents. The data were analyzed using multiple linear regression and determination tests. Based on the results of data analysis, the results of the F test indicate that the quality of service, product quality and promotion mix simultaneously have a significant and positive effect on purchasing decisions and have an effect on purchasing decisions for Waroeng Om products, Malang City. Furthermore, the results of the t-test indicate that service quality, product quality and promotion mix partially have a significant and positive effect on purchasing decisions for Waroeng Om products, Malang City. The results of the determination test show that the percentage is 60.5%, which purchasing decisions can be influenced by service quality, product quality and promotion mix. Management should pay more attention to consumer attitudes and behavior in the purchase stage, one of which is by providing good quality products so that consumers will easily buy Waroeng Om Malang products more precisely and quickly. Keywords: Purchase Decision, Service Quality, Product Quality, Promotional mix